Flame-retardant liquid silica gel for data line and preparation method of flame-retardant liquid silica gel
By using a dynamic intelligent system of composite flame retardants and crosslinking agents, the material interface compatibility and crosslinking density of the data cable sheath are optimized, solving the problem of balancing flame retardancy efficiency and mechanical properties in high-power fast charging environments, and achieving high-efficiency flame retardancy and long-term reliability of the sheath.
Patent Information
- Application Number
- CN202510974835.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-11-04
AI Technical Summary
Existing data cable sheath materials are prone to overheating and catching fire under high-power fast charging conditions. The addition of traditional flame retardants leads to deterioration of processing rheology and degradation of mechanical properties, making it difficult to balance flame retardancy efficiency and mechanical properties.
By employing a dynamic intelligent system of composite flame retardants and crosslinking agents, and precisely controlling the timing and process of flame retardant addition, a nanoscale encapsulation structure is formed, optimizing the material interface compatibility and crosslinking density. Combined with dynamic humidity, temperature-segmented vulcanization and cooling strategies, the material's adaptability and product lifespan consistency are achieved.
It significantly improves the flame retardancy and mechanical properties of the data cable sheath, reduces phase separation, avoids thermal aging cracks, and ensures long-term product reliability and shape stability.
Smart Images

Figure BDA0005501109480000081
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of flame-retardant liquid silicone, and particularly relates to a flame-retardant liquid silicone for a data line. BACKGROUND
[0002] With the development of consumer electronic devices towards high-power fast charging, the risk of overheating and fire caused by the increased current load of the data line has significantly increased. Although the traditional PVC or TPE sheath material has basic flame retardancy, it is prone to hardening and cracking after long-term use, and releases a large amount of toxic halogen gas during combustion.
[0003] Furthermore, in the prior art, the demand for high flame retardancy forces an increase in the amount of flame retardant, but this causes deterioration of the processing rheology, attenuation of the mechanical properties, and decline in long-term reliability, forming a technical dead loop that is difficult to optimize synergistically. For example, conventional silicone achieves V-0 level flame retardancy by adding single aluminum hydroxide, but high addition amount leads to reduction in the tensile strength of the sheath and reduction in the bending life. At the same time, the inorganic flame retardant has poor compatibility with the silicone, and phase separation occurs during extrusion, resulting in pits on the surface of the sheath.
[0004] Based on the above, we propose a flame-retardant liquid silicone for a data line and a preparation method thereof, which specifically solves the problems existing in the prior art. SUMMARY
[0005] The application aims to provide a flame-retardant liquid silicone for a data line and a preparation method thereof, which reconstructs the mechanism of incorporating flame retardants into silicone crosslinking from the molecular scale, integrates formula design and process control into a dynamic intelligent system, thereby fundamentally breaking through the contradiction between flame retardant efficiency and mechanical properties in the prior art, achieving comprehensive optimization of the stability of the material interface, the self-adaptability of the process response, and the consistency of the product life, and significantly improving the overall reliability of the data line sheath.
[0006] To achieve the above-mentioned purpose, the application adopts the following technical scheme:
[0007] A flame-retardant liquid silicone for a data line, wherein the outer sheath of the data line is made of the flame-retardant liquid silicone, and the raw material formula of the flame-retardant liquid silicone consists of 100 parts of base glue, 2-7 parts of crosslinking agent, 15-55 parts of composite flame retardant, 25-65 parts of reinforcing filler, 0.05-0.8 parts of platinum catalyst, and 0.5-12 parts of process additive, in terms of mass fraction.
[0008] The composite flame retardant is composed of inorganic flame retardant and organic flame retardant in a ratio of 1:0.3-1:1.2, the reinforcing filler comprises hydrophobic fumed silica, and the platinum catalyst is a complex of chloroplatinic acid and vinyl siloxane.
[0009] Preferably, the base glue is a vinyl-terminated polydimethylsiloxane with a vinyl content of 0.15-1.2 mol% and a viscosity of 800-12,000 mPa·s; the base glue is compounded from a high-viscosity component and a low-viscosity component, wherein the viscosity of the high-viscosity component is 5,000-12,000 mPa·s, the viscosity of the low-viscosity component is 100-2,000 mPa·s, and the mass ratio of the two is 1:0.8-1:1.5; the high-viscosity component provides mechanical strength support, and the low-viscosity component improves processing fluidity, thereby synergistically ensuring the extensibility of the liquid silicone during data line extrusion molding and the tear resistance of the cured product, which is not less than 8 MPa.
[0010] Preferably, the crosslinking agent is a hydrogen-containing silicone oil with a hydrogen content of 0.18-1.8 wt%, and the molar ratio of Si-H groups in the molecular chain to vinyl groups in the base glue is 0.85:1-1.65:1; the crosslinking agent comprises a mixture of side-chain hydrogen-containing and end-group hydrogen-containing types, with the side-chain hydrogen-containing type accounting for 60-90 wt% and the end-group hydrogen-containing type accounting for 10-40 wt%; by adjusting the crosslinking network density, the hardness of the cured product is in the range of Shore A 30-55, and the elongation at break is ≥350%; when the addition amount of the crosslinking agent is 3.2-6 parts, the curing rate and flexibility can be simultaneously optimized.
[0011] Preferably, the inorganic flame retardant in the composite flame retardant is a mixture of aluminum hydroxide and zinc borate with a mass ratio of 6:1-10:1 and a particle size D50 of 1-8 μm; the organic flame retardant is at least one selected from phosphorus acid tris(2-chloroethyl) ester and dimethyl methylphosphonate, and is surface-modified by a silane coupling agent; when the addition amount of the composite flame retardant is 32-48 parts, the data line passes the UL94 V-0 level flame retardant test, the limiting oxygen index is ≥32%, and the smoke density rating during combustion is ≤75; the inorganic flame retardant and the organic flame retardant form a synergistic barrier layer in the range of 200-300℃, inhibiting heat conduction and flammable gas release.
[0012] Preferably, the reinforcing filler is composed of hydrophobic fumed silica and silicon powder, the specific surface area of the hydrophobic fumed silica is 180-380 m 2 / g, and it is modified by hexamethyldisilazane with a hydroxyl residue rate of ≤35%; the particle size of the silicon powder is 5-25 μm, and the Mohs hardness is ≥7; the mass ratio of the hydrophobic fumed silica to the silicon powder is 1:0.4-1:1.1, and the total addition amount is 35-58 parts; the reinforcing filler increases the thixotropic index of the liquid silicone to 4.5-6.0 through the high surface energy effect, inhibits the sedimentation of the flame retardant, and makes the tensile strength after curing ≥4.5 MPa.
[0013] Preferably, the platinum element content in the platinum catalyst is 800-3200 ppm, and a solution with a mass concentration of 0.1-0.5% is prepared using isopropyl alcohol as a solvent; the process aid includes an adhesion promoter, a smoke suppressant, and a colorant, wherein the adhesion promoter is γ-glycidoxypropyltrimethoxysilane, and the addition amount is 0.3-2 parts, so as to improve the adhesion of the silica gel layer and the data line shielding layer; the smoke suppressant is a composite of ammonium molybdate and red iron oxide, and the mass ratio is 1:0.2-1:0.6, and the addition amount is 1-6 parts; and the colorant is a high-temperature-resistant phthalocyanine blue, and the addition amount is 0.2-0.9 parts.
[0014] A preparation method of a flame-retardant liquid silica gel for data lines, which is used for preparing the flame-retardant liquid silica gel described above, comprises the following steps:
[0015] S1, 100 parts of the base glue in claim 1 and 25-65 parts of reinforcing fillers are added to a planetary stirrer, and stirring is performed at 45-80 r / min under a vacuum degree of-0.08 to-0.1 MPa for 25-50 minutes to form a premixed glue body;
[0016] S2, the premixed glue body is heated to 70-90℃, 15-55 parts of a composite flame retardant is added, and vacuum stirring is continued until the viscosity reaches 120,000±15,000 mPa·s;
[0017] S3, after being cooled to <40℃, 2-7 parts of a crosslinking agent, 0.05-0.8 parts of a platinum catalyst, and 0.5-12 parts of a process aid are added, and high-speed dispersion is performed at 200-400 r / min under nitrogen protection for 10-20 minutes;
[0018] S4, the mixed glue is injected into the hopper of a double-screw extruder, and a sheath layer with a thickness of 0.4-1.8 mm is formed on the data line conductor through a die at a temperature interval of 60-95℃;
[0019] S5, stepwise vulcanization is performed in a hot air tunnel at 120-160℃ for 3-15 minutes, and the stepwise temperature gradient is: 120℃×(30% of the total time)→140℃×(50% of the total time)→160℃×(20% of the total time);
[0020] S6, after water cooling and shaping, the data line is wound and collected, and the cooling water temperature is 10-25℃.
[0021] Preferably, the vacuum stirring process in step S1 adopts a three-stage intensity gradient control: in the first stage, stirring is performed at 45-55 r / min for 8-15 minutes to preliminarily wet and disperse the reinforcing fillers; in the second stage, the stirring speed is increased to 60-70 r / min, and the vacuum degree is maintained at-0.095±0.005 MPa for 12-20 minutes to eliminate micro-bubble aggregation; and in the third stage, the stirring speed is reduced to 50-60 r / min for final mixing for 5-15 minutes, and at this time, the torque fluctuation amplitude of the system is ≤5 N·m.
[0022] Preferably, the step S5 of segmenting vulcanization is carried out in a closed hot air circulating tunnel, and its humidity control system implements a double compensation mechanism: at the 120 DEG C stage, the relative humidity is maintained at 20%-25% to pre-solidify the surface layer of the sheath layer to form a gas-permeable film with a porosity of 10%-15%; at the 140 DEG C stage, a nitrogen gas carrying humid gas flow is introduced to increase the humidity to 40%-45% to promote the penetration of the crosslinking agent into the deep layer; and at the 160 DEG C stage, dry air is switched to accelerate the final solidification, with a dew point of less than or equal to -40 DEG C.
[0023] Technical effects and advantages of the present application:
[0024] By precisely controlling the addition timing of the composite flame retardant, the chemical bonding between the silica gel polymer chain and the inorganic microparticles is promoted; the specific mechanism is that the control optimizes the dispersion uniformity of the flame retardant in the silica gel matrix, forms a nano-scale wrapping structure, thereby reducing the interfacial tension and energy barrier; this effectively improves the mixing compatibility of the flame retardant and the silica gel, reduces the phase separation phenomenon, significantly enhances the molecular interfacial bonding strength of the sheath material, and further synchronously improves the flame retardancy and mechanical properties without causing material defects;
[0025] A dynamic humidity and temperature segmented vulcanization process is adopted, and a nonlinear integral model is used to simulate the evolution of catalyst activity; mechanism level: this design compensates for the attenuation effect of the platinum catalyst, establishes continuous reaction enthalpy control, and ensures the uniform advancement of the crosslinking reaction in the time and space dimensions; thus, local unvulcanized areas caused by catalyst deactivation are avoided, and the crosslinking density of the silica gel molecular chain network reaches an ideal balance, fundamentally inhibiting the thermal aging cracks of the sheath layer caused by uneven stress. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. The specific embodiments described herein are only used to explain the present application, and are not used to limit the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0027] The present application proposes a flame-retardant liquid silica gel for data lines and a preparation method thereof, which reconstructs the mechanism of incorporating flame retardants into silica gel crosslinking from the molecular scale, integrates formula design and process control into a dynamic intelligent system, thereby fundamentally breaking through the contradiction in the prior art that flame retardation efficiency and mechanical properties are difficult to be balanced, realizing the comprehensive optimization of the stability of the material interface, the self-adaptability of the process response, and the consistency of the product life, and significantly improving the overall reliability of the data line sheath;
[0028] The data line uses the fire-retardant liquid silicone rubber to make the outer sheath of the data line, and the formula is composed of base glue, crosslinking agent, composite flame retardant, reinforcing filler, platinum catalyst and process additive.
[0029] The composite flame retardant is composed of inorganic flame retardant and organic flame retardant in a ratio of 1:0.3-1:1.2, the reinforcing filler comprises hydrophobic fumed silica, and the platinum catalyst is a complex of chloroplatinic acid and vinyl siloxane;
[0030] The base glue is vinyl-terminated polydimethylsiloxane with a vinyl content of 0.15-1.2 mol% and a viscosity of 800-12,000 mPa·s; the base glue is compounded from a high-viscosity component and a low-viscosity component, wherein the viscosity of the high-viscosity component is 5,000-12,000 mPa·s, the viscosity of the low-viscosity component is 100-2,000 mPa·s, and the mass ratio of the two is 1:0.8-1:1.5; the high-viscosity component provides mechanical strength support, and the low-viscosity component improves the processing fluidity, thereby synergistically ensuring the ductility of the liquid silicone rubber during the extrusion molding of the data line and the tear resistance of the cured product of not less than 8 MPa.
[0031] It should be noted that the crosslinking agent is hydrogen-containing silicone oil with a hydrogen content of 0.18-1.8 wt%, and the molar ratio of Si-H groups in the molecular chain to vinyl groups in the base glue is 0.85:1-1.65:1; the crosslinking agent comprises a mixture of side-chain hydrogen-containing type and end-group hydrogen-containing type, the proportion of the side-chain hydrogen-containing type is 60-90 wt%, and the proportion of the end-group hydrogen-containing type is 10-40 wt%, the hardness of the cured product is in the range of Shore A 30-55 by adjusting the crosslinking network density, and the elongation at break is ≥350%; when the addition amount of the crosslinking agent is 3.2-6 parts, the curing rate and flexibility can be optimized simultaneously.
[0032] The inorganic flame retardant in the composite flame retardant is a mixture of aluminum hydroxide and zinc borate in a mass ratio of 6:1-10:1, and the particle size D50 is 1-8 μm; the organic flame retardant is at least one selected from phosphorus acid tris(2-chloroethyl) ester and dimethyl methylphosphonate, and is surface modified by a silane coupling agent; when the addition amount of the composite flame retardant is 32-48 parts, the data line passes the UL94 V-0 level flame retardant test, the limiting oxygen index is ≥32%, and the smoke density rating during combustion is ≤75; the inorganic flame retardant and the organic flame retardant form a synergistic barrier layer in the range of 200-300℃, which inhibits heat conduction and flammable gas release; the reinforcing filler is composed of hydrophobic fumed silica and silicon powder, the specific surface area of the hydrophobic fumed silica is 180-380 m 2 / g, modified by hexamethyldisilazane, with a hydroxyl residual rate of ≤ 35%; the particle size of the silicon powder is 5-25 μm, and the Mohs hardness is ≥ 7; the mass ratio of the hydrophobic fumed silica to the silicon powder is 1:0.4-1:1.1, and the total additive amount is 35-58 parts; the reinforcing filler improves the thixotropic index of the liquid silicone to 4.5-6.0 through a high surface energy effect, inhibits the sedimentation of the flame retardant, and makes the tensile strength after curing ≥ 4.5 MPa.
[0033] The platinum content in the platinum catalyst is 800-3,200 ppm, and a solution with a mass concentration of 0.1-0.5% is prepared using isopropyl alcohol as a solvent; the process aid includes an adhesion promoter, a smoke suppressant, and a colorant, wherein the adhesion promoter is γ-glycidoxypropyltrimethoxysilane, the additive amount is 0.3-2 parts, and the adhesion promoter is used to improve the adhesion of the silicone layer to the data line shielding layer; the smoke suppressant is a composite of ammonium molybdate and red iron oxide, the mass ratio is 1:0.2-1:0.6, and the additive amount is 1-6 parts; and the colorant is a high-temperature-resistant phthalocyanine blue, and the additive amount is 0.2-0.9 parts.
[0034] In addition, it should be noted that the data line includes an inner conductor layer, an insulating layer, and a metal shielding layer, wherein the insulating layer is foamed polyethylene with a density of 0.25-0.45 g / cm 3 ; the metal shielding layer is a tinned copper braid layer with a coverage rate of ≥ 85%; the outer surface of the flame-retardant liquid silicone sheath layer is provided with anti-slip lines with a line depth of 0.1-0.3 mm, a line density of 8-15 lines / cm, and 0.1-0.8 parts of nano titanium dioxide is added to improve the anti-ultraviolet aging property, so that the attenuation rate of the flame-retardant property of the data line is ≤ 10% after aging for 1,000 hours in an environment of 85°C / 85% RH.
[0035] The above-mentioned method for preparing a flame-retardant liquid silicone for a data line is as follows:
[0036] S1, 100 parts of the base glue of claim 1 and 25-65 parts of reinforcing filler are added to a planetary mixer, and stirred at 45-80 r / min under a vacuum degree of -0.08 to -0.1 MPa for 25-50 minutes to form a premixed glue body; the vacuum stirring process in step S1 adopts a three-stage intensity gradient control: in the first stage, the stirring speed is 45-55 r / min for 8-15 minutes to preliminarily wet and disperse the reinforcing filler; in the second stage, the stirring speed is increased to 60-70 r / min and maintained at a vacuum degree of -0.095±0.005 MPa for 12-20 minutes to eliminate micro-bubble aggregation; in the third stage, the stirring speed is reduced to 50-60 r / min for final mixing for 5-15 minutes, at which time the torque fluctuation amplitude of the system is ≤5 N·m. The planetary mixer paddle is configured with double-layer sawtooth shear discs and a reverse wall scraper, the paddle-pot wall gap is controlled at 0.8-1.2 mm, and the glue temperature rise is monitored in real time by a temperature sensor, with a glue temperature rise ≤7℃. This gradient strategy makes the uniformity of the dispersion of hydrophobic fumed silica reach more than 96%, the thixotropic index of the premixed glue body is stably in the interval of 5.2-5.8, and ensures that no local aggregation occurs when the flame retardant is added subsequently, which shortens the process time by 30% and reduces the energy consumption by 18% compared with conventional single-speed mixing;
[0037] S2, the premixed glue body is heated to 70-90℃, 15-55 parts of a composite flame retardant is added, and vacuum stirring is continued until the viscosity reaches 120,000±15,000 mPa·s;
[0038] S3, after being cooled to <40℃, 2-7 parts of a crosslinking agent, 0.05-0.8 parts of a platinum catalyst and 0.5-12 parts of a process aid are added, and high-speed dispersion is carried out at 200-400 r / min for 10-20 minutes under nitrogen protection;
[0039] S4, the mixed glue is injected into the hopper of a twin-screw extruder, and a sheath layer with a thickness of 0.4-1.8 mm is formed on the data line conductor through a die at a temperature interval of 60-95℃; the rheological balance index of the extrusion process is regulated according to the following formula:
[0040] wherein, Ψ is the extrusion stability index, the control value is 3.5±0.4, γ is the screw shear rate, ρ filler is the volume fraction of the reinforcing filler, P hydro is the proportion of hydrophobic fumed silica, μmelt is the melt viscosity, and Dnozzle is the diameter of the extrusion die; the index correlates the material flowability and filler dispersibility, and when Ψ=3.5:
[0041] the sharkskin phenomenon is eliminated, and the surface roughness Ra of the sheath is <0.8 μm;
[0042] the distribution variation coefficient of the reinforcing filler in the sheath cross-section is ≤7.5%;
[0043] S5, segmental vulcanization in a 120-160℃ hot air tunnel for 3-15 minutes, with a segmental temperature gradient of: 120℃ x (30% of total time)→ 140℃ x (50% of total time)→ 160℃ x (20% of total time); the segmental vulcanization of step S5 is performed in a closed hot air circulation tunnel, with its humidity control system implementing a double compensation mechanism: maintaining a relative humidity of 20%-25% at the 120℃ stage to pre-solidify the surface layer of the sheath and form a gas-permeable film with a porosity of 10%-15%; introducing a nitrogen-carrying humid gas flow at the 140℃ stage to increase the humidity to 40%-45% to promote the penetration of cross-linking agents into the deep layer; switching to dry air (dew point ≤-40℃) at the 160℃ stage to accelerate the final solidification; the hot air flow rate is implemented in a zoned regulation: 0.5-1.0 m / s in the preheating zone, 2.0-3.5 m / s in the reaction zone, and 4.0-6.0 m / s in the cooling zone, with a wind speed variation coefficient ≤8%. This environmental control improves the activation efficiency of platinum catalyst to 92%, shortens the vulcanization induction period by 40 seconds, and makes the product longitudinal hardness deviation ≤±2;
[0044] S6, after water cooling and shaping, winding the take-up, with a cooling water temperature of 10-25℃; during the water cooling and shaping of step S6, dynamic temperature-pressure coupling control is implemented: the cooling water tank is divided into a rapid cooling section (10-15℃) and a slow cooling section (20-25℃), the rapid cooling section has a water flow rate of 3-5 m / s and applies a water pressure of 0.3-0.6 MPa to increase the crystallization rate of the sheath surface by 1.8 times; the slow cooling section adopts a laminar flow mode (flow rate ≤0.8 m / s) to release thermal stress. The shaping mold is provided with a micro-oscillation mechanism with an amplitude of 0.05-0.12 mm and a frequency of 15-25 Hz to suppress the warping deformation caused by the shrinkage difference between the flame retardant and the silica gel. After water cooling, synchronous implementation of infrared drying (wavelength 3-5 μm) and static elimination (voltage 5-8 kV) is implemented, with the final product roundness deviation ≤0.03 mm and surface resistivity ≤10 9 Ω / sq, meeting the antistatic requirements of medical-grade electronic equipment.
[0045] According to the above, the specific implementation is as shown in the following table:
[0046]
[0047] In the above table, Example 1: using a conventional silica gel and aluminum magnesium hydroxide flame retardant system, the vulcanization process is not segmented and humidity controlled. Only a single temperature water bath is used in the cooling stage. Results: the flame retardancy reaches UL94 V-0 level but the tensile strength is only 3.2 MPa, with >5 μm micropores appearing on the surface (observed by SEM), and breaking after 5000 bends;
[0048] Example 2: Using phenyl silica gel to improve heat resistance, adding hydrophobic treatment phosphorus-nitrogen compound to composite flame retardant; humidity gradient control (25%→45%RH) is implemented in the vulcanization stage, and rapid and slow two-stage coupling micro-vibration shaping is used for cooling. Results: The LOI value is increased to 42%, the tensile strength reaches 6.8 MPa, and the surface roughness Ra is less than 0.1 μm, and no cracks are found after 50,000 bending tests;
[0049] Example 3: For the high-voltage data line requirements of electric vehicles, fluorosilicone rubber matrix is used, the amount of flame retardant is increased to 65 parts, and silicon carbide whiskers are introduced for reinforcement. In the cooling stage, infrared drying and static elimination are superimposed. Results: Arc resistance > 180s (IEC61621 standard), elongation retention rate > 85% after high temperature aging (200℃×168h), but the cost is increased by 40%.
[0050] The specific performance of the above examples is as follows:
[0051] Performance Indicators Example 1 Example 2 Example 3 Test Standards Limiting Oxygen Index (LOI) 32% 42% 48% ASTM D2863 Tensile Strength 3.2 MPa 6.8 MPa 7.5 MPa ISO 37 Flex Life 5,000 cycles > 50,000 cycles 45,000 cycles IEC 62133 Surface Defect Density 15 / cm 2 ]] <1 per cm 2 ]] 3 cells / cm 2 ]] SEM 500x field Volume Resistivity 10 12 Ω·cm 10 9 Ω·cm 10 10 Ω·cm ASTM D257 Process Energy Consumption Baseline (100%) 82% 105% Kilowatt hours per Kilometer of Cable
[0052] According to the above, example 2 synchronously improves LOI and tensile strength by 113% through composite flame retardant gradient dispersion and dynamic vulcanization: phosphorus-nitrogen flame retardant forms an expanded carbon layer in silica gel, and gradient humidity promotes cross-linked network to wrap flame-retardant particles, avoiding strength decay; Example 3 causes the flexibility of the matrix to decrease due to excessive flame retardant.
[0053] Example 2 uses the rapid and slow cooling coupling micro-vibration of the claim: the rapid cooling segment suppresses the crystallization speed of silica gel through high-pressure water penetration, and the slow cooling segment releases thermal stress through laminar flow, reducing surface defects by 99%, while example 1 causes micropore aggregation due to uneven cooling.
[0054] Example 3 achieves ultra-high flame retardancy (LOI 48%), but the viscosity of fluorosilicone rubber and high filler content causes the viscosity to rise, requiring additional peroxide vulcanization (increasing the risk of poisoning) and increased energy consumption; Example 2 has the optimal comprehensive cost under the premise of maintaining UL94 V-0 level.
[0055] Conclusion: Example 2 fully implements the gradient process and interface regulation strategy of the claim, verifying the synergistic mechanism of formula collaborative design (phenyl silica gel + phosphorus-nitrogen flame retardant) and dynamic control (segmented vulcanization / cooling), becoming the optimal solution in terms of performance and cost. The three examples cover consumer electronics to industrial application scenarios, proving the universality of the invention;
[0056] In summary, the following advantages are provided:
[0057] Interface compatibility enhancement (based on synergistic effect of composite flame retardant): The present application promotes the chemical bonding between the silica gel polymer chain and the inorganic microparticles by precisely controlling the addition timing of the composite flame retardant; the specific mechanism: this control optimizes the uniformity of the dispersion of the flame retardant in the silica gel matrix, forming a nano-scale wrapping structure, thereby reducing the interfacial tension and energy barrier; this effectively improves the mixing compatibility of the flame retardant and the silica gel, reduces the phase separation phenomenon, significantly enhances the molecular interface bonding strength of the sheath material, and in turn synchronously improves the flame retardancy and mechanical properties without causing material defects;
[0058] Crosslinking uniformity optimization (based on gradient vulcanization energy regulation): The present application adopts a dynamic humidity and temperature segmented vulcanization process, and simulates the evolution of catalyst activity through a nonlinear integral model; Mechanism level: This design compensates for the attenuation effect of platinum catalyst, establishes continuous reaction enthalpy control, and ensures uniform advancement of crosslinking reaction in time and space dimensions; thus avoiding local unvulcanized areas caused by catalyst deactivation, making the crosslinking density of the silica gel molecular chain network reach an ideal balance, and fundamentally inhibiting thermal aging cracks in the sheath layer caused by uneven stress;
[0059] Rheological stability improvement (based on synergistic control of extrusion process): The present application regulates the extrusion process by coupling the rheological balance index, integrating the hydrophobicity of fillers and equipment geometric parameters; Mechanism: This regulation mechanism balances the melt shear force and filler dispersion force, inhibiting the elastic deformation of polymer chains when flowing through the die; thus maintaining the steady flow of material viscoelasticity, reducing local shear heat and tensile strain, making the reinforcing filler uniformly distributed in the silica gel matrix, thereby eliminating extrusion defects (such as sharkskin effect), and ensuring the consistency of the sheath layer microstructure;
[0060] Thermal stress release mechanism improvement (based on dynamic cooling strategy): The present application implements temperature and pressure partition coupling control during the cooling and shaping stage, and combines with micro-vibration shaping; Mechanism level: This design creates a temperature gradient induced phase change process, simultaneously utilizing physical vibration to disperse crystallization stress; This optimizes the transition kinetics of silica gel from molten state to solid state, allowing the polymer chain to arrange in order without generating residual internal stress, while compensating for the thermal expansion difference of different components (such as flame retardant and silica gel); thus effectively preventing the shrinkage or warping of the sheath during the cooling process, ensuring the long-term shape stability of the product.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent replacements to some technical features, as long as they are within the spirit and principles of the present application. Any modification, equivalent replacement, improvement, etc. made within the scope of the present application shall be included in the protection scope of the present application.
Claims
1. A flame-retardant liquid silicone for a data line, characterized by comprising: The outer sheath of the data line is made of flame-retardant liquid silicone, and the raw material formula of the flame-retardant liquid silicone is composed of 100 parts of base glue, 2-7 parts of crosslinking agent, 15-55 parts of composite flame retardant, 25-65 parts of reinforcing filler, 0.05-0.8 parts of platinum catalyst and 0.5-12 parts of process additive. The composite flame retardant is composed of inorganic flame retardant and organic flame retardant in a ratio of 1:0.3-1:1.2, and the reinforcing filler contains hydrophobic fumed silica, and the platinum catalyst is a complex of chloroplatinic acid and vinyl siloxane.
2. The flame-retardant liquid silicone rubber for data line according to claim 1, characterized in that, The base glue is vinyl-terminated polydimethylsiloxane with a vinyl content of 0.15-1.2 mol% and a viscosity of 800-12,000 mPa·s; the base glue is compounded from a high-viscosity component and a low-viscosity component, wherein the viscosity of the high-viscosity component is 5,000-12,000 mPa·s, the viscosity of the low-viscosity component is 100-2,000 mPa·s, and the mass ratio of the two is 1:0.8-1:1.5; the high-viscosity component provides mechanical strength support, and the low-viscosity component improves processing fluidity, thereby ensuring the ductility of the liquid silicone during data line extrusion molding and the tear resistance of the cured product of not less than 8 MPa.
3. The flame-retardant liquid silicone rubber for data line according to claim 1, characterized in that, The crosslinking agent is hydrogen-containing silicone oil with a hydrogen content of 0.18-1.8 wt%, and the molar ratio of Si-H groups in the molecular chain to vinyl groups in the base glue is 0.85:1-1.65:1; the crosslinking agent contains a mixture of side-chain hydrogen-containing type and end-group hydrogen-containing type, with the side-chain hydrogen-containing type accounting for 60-90 wt% and the end-group hydrogen-containing type accounting for 10-40 wt%; by adjusting the crosslinking network density, the hardness of the cured product is in the range of Shore A 30-55, and the elongation at break is ≥350%; when the addition amount of the crosslinking agent is 3.2-6 parts, the curing rate and flexibility can be simultaneously optimized.
4. The flame-retardant liquid silicone rubber for data line according to claim 1, characterized in that, The inorganic flame retardant in the composite flame retardant is a mixture of aluminum hydroxide and zinc borate in a mass ratio of 6:1-10:1, and the particle size D50 is 1-8 μm; the organic flame retardant is a phosphorus-based flame retardant selected from at least one of tris(2-chloroethyl) phosphate and dimethyl methylphosphonate, and is surface-modified by a silane coupling agent; when the addition amount of the composite flame retardant is 32-48 parts, the data line passes the UL94 V-0 level flame retardant test, the limiting oxygen index is ≥32%, and the smoke density rating during combustion is ≤75; the inorganic flame retardant and the organic flame retardant form a synergistic barrier layer in the range of 200-300℃, which inhibits heat conduction and flammable gas release.
5. The flame retardant liquid silicone rubber for data line according to claim 1, characterized in that, The reinforcing filler is composed of hydrophobic fumed silica and silica powder, the specific surface area of the hydrophobic fumed silica is 180-380m 2 / g, the hydrophobic fumed silica is modified by hexamethyldisilazane, and the residual rate of hydroxyl is less than or equal to 35%; the particle size of the silica powder is 5-25μm, and the Mohs hardness is greater than or equal to 7; the mass ratio of the hydrophobic fumed silica to the silica powder is 1:0.4-1:1.1, and the total addition amount is 35-58 parts; the reinforcing filler improves the thixotropic index of the liquid silica gel to 4.5-6.0 through the high surface energy effect, inhibits the sedimentation of the flame retardant, and makes the tensile strength after curing greater than or equal to 4.5MPa.
6. The flame-retardant liquid silicone rubber for data line according to claim 1, characterized in that, The platinum catalyst contains 800-3200 ppm of platinum, and is prepared into a solution with a mass concentration of 0.1-0.5% using isopropyl alcohol as the solvent; the process additive includes adhesion promoter, smoke suppressant and colorant, wherein the adhesion promoter is γ-glycidyl ether oxypropyl trimethoxysilane with an addition amount of 0.3-2 parts to improve the adhesion between the silicone layer and the data line shielding layer; the smoke suppressant is a composite of ammonium molybdate and red iron oxide in a mass ratio of 1:0.2-1:0.6 with an addition amount of 1-6 parts; and the colorant is high-temperature-resistant phthalocyanine blue with an addition amount of 0.2-0.9 parts.
7. A method for preparing a flame-retardant liquid silicone for a data line, characterized by, The method is used for preparing the flame-retardant liquid silicone rubber of any one of claims 1-6, comprising the following steps: S1, 100 parts of the base glue of claim 1 and 25-65 parts of reinforcing filler are added into a planetary mixer, and stirring is carried out at 45-80 r / min under a vacuum degree of-0.08 to-0.1 MPa for 25-50 minutes to form a premixed glue body; S2, the premixed glue body is heated to 70-90℃, 15-55 parts of the composite flame retardant is added, and vacuum stirring is continued until the viscosity reaches 120,000±15,000 mPa·s; S3, after being cooled to <40℃, 2-7 parts of a crosslinking agent, 0.05-0.8 parts of a platinum catalyst and 0.5-12 parts of a process aid are added, and high-speed dispersion is carried out at 200-400 r / min under nitrogen protection for 10-20 minutes; S4, the mixed glue is injected into the hopper of a double-screw extruder, and a sheath layer with a thickness of 0.4-1.8 mm is formed on the data line conductor through a die at a temperature interval of 60-95℃; S5, sectional vulcanization is carried out in a hot air tunnel at 120-160℃ for 3-15 minutes, and the sectional temperature gradient is: 120℃×(30% of the total time)→140℃×(50% of the total time)→160℃×(20% of the total time); S6, after water cooling and shaping, the line is wound and cooled, and the cooling water temperature is 10-25℃.
8. The method of claim 7, wherein the flame-retardant liquid silicone for a data line is prepared by adding 0.1 to 0.5 parts by weight of the flame retardant to 100 parts by weight of the base silicone. The vacuum stirring process in step S1 adopts a three-stage intensity gradient control: in the first stage, stirring is carried out at 45-55 r / min for 8-15 minutes to preliminarily wet and disperse the reinforcing filler; in the second stage, the speed is increased to 60-70 r / min and maintained at a vacuum degree of-0.095±0.005 MPa for 12-20 minutes to eliminate micro-bubble aggregation; in the third stage, the speed is reduced to 50-60 r / min for final mixing for 5-15 minutes, at which time the torque fluctuation amplitude of the system is ≤5 N·m.
9. The method of claim 7, wherein the flame-retardant liquid silicone for a data line is prepared by adding 0.1 to 0.5 parts by weight of the flame retardant to 100 parts by weight of the base silicone. The sectional vulcanization of step S5 is carried out in a closed hot air circulation tunnel, and its humidity control system executes a double compensation mechanism: at the 120℃ stage, the relative humidity is maintained at 20%-25% to make the sheath layer surface preliminarily cured to form a gas-permeable film with a porosity of 10%-15%; at the 140℃ stage, nitrogen gas is introduced to increase the humidity to 40%-45% to promote the penetration of the crosslinking agent into the deep layer; at the 160℃ stage, dry air is switched to, and the dew point is ≤-40℃ to accelerate the final curing.
Citation Information
Patent Citations
Bicomponent addition high-flame-retardant silicone rubber and preparation method thereof
CN103333506A